A Study of Promoting Gender Equality to Prevent Violence against Women: Exploring the Impact of Gender Inequalities and Violence against Women (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The relationship between gender and violence is complex. The different roles and behaviours of females and males, children as well as adults, are shaped and reinforced by gender norms within society. These are social expectations that define appropriate behaviour for women and men (e.g. in some societies, being male is associated with taking risks, being tough and aggressive and having multiple sexual partners). Differences in gender roles and behaviours often create inequalities, whereby one gender becomes empowered to the disadvantage of the other. Thus, in many societies, women are viewed as subordinate to men and have a lower social status, allowing men control over, and greater decision-making power than, women. Gender inequalities have a large and wide-ranging impact on society. Violence is coordinated explicitly against a lady since she is a lady, or influences women lopsidedly. It incorporates, yet isn't constrained to, physical, sexual and mental mischief (counting terrorizing, enduring, intimidation, or potentially hardship of freedom inside the family, or inside the general network). It incorporates that Violence which is executed or approved by the state. This broadly acknowledged meaning of sex based violence is presently regularly extended to incorporate viciousness that outcomes from unequal power relations among men and between women (e.g. homophobic Violence).